Implementasi Pendekatan Saintifik Kurikulum 2013 Revisi Pada Madrasah Aliyah Peminatan Ilmu Keagamaan di Aceh - M. Yusuf; Ismail Darimi (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2021)
The components of the scientific approach in learning emphasize more on observing, asking, trying, reasoning, and communicating activities. The ultimate goal of learning, all competencies are balanced between attitudes, skills, and knowledge. Initial observations in Madrasah Aliyah that there is a Religious Science Specialization in Aceh partially have not implemented learning with the 2013 Curriculum Scientific Approach, the learning process in the classroom is also still teacher-centered and the assessment has not fully used authentic assessment. This field research uses a qualitative approach, research procedures that produce descriptive data on teacher readiness in madrasah. The results of the study indicate that the readiness of teachers who teach in the religious sciences majors at Madrasah Aliyah in Aceh in implementing the scientific approach to the 2013 curriculum has made various efforts, both in learning planning, learning implementation, and learning assessment, such as compiling a learning implementation plan that is in accordance with scientific learning. The implementation of learning is not optimal, this is because there are several factors, including in formulating scientific learning must be supported by all sectors, both media, methods, and student readiness. So the implementation in the field is still constrained by the availability of supporting media, if any, the number is very limited. The results of this study recommend policymakers provide support for learning media, at least in the form of policies that support independent and high-achieving madrasas.